Student Risk Factors Identified by School Counselors and Student Achievement - Couillard, Darren; Garnett, Julie; Hutchins, Angel; Fawcett, Mary L.; Maycock, George (Alberta Journal of Educational Research, 2006)
The increasing emphasis in the United States on high-stakes testing for students and schools generates a great deal of quantitative data, but these data are less frequently linked to other data that are more difficult to obtain such as data on risk factors that may affect how students do on these tests. To make such comparisons, a group of counselors and counselor educators targeted a small urban school district to conduct a quantitative study of the relationship between grades, standard achievement test scores, and risk factors for K-12 students. Students in grades 4, 6, 8, and 9 were randomly selected and data were gathered from school counselors on relevant descriptive information and student risk factors. More than 50% of the students in this sample were affected by at least one risk factor. Students experiencing higher numbers of risk factors tended to have lower achievement test scores and lower grade point averages (GPAs) and were also likely to be male, Hispanic, or Black; to be receiving special education services; to have high rates of absent or tardy days; to have many suspensions or discipline reports; to have single, deceased, or stepparents; and/or to have free or reduced-price lunch status. This article discusses the research process, findings, and implications for educators, particularly in the light of other findings that the effects of some risk factors may be mitigated by the actions of school counselors.